2010
DOI: 10.1093/ndt/gfq138
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise among participants in the Dialysis Outcomes and Practice Patterns Study (DOPPS): correlates and associated outcomes

Abstract: Results from an international study of haemodialysis patients indicate that regular exercise is associated with better outcomes in this population and that patients at facilities offering exercise programmes have higher odds of exercising. Dialysis facility efforts to increase patient physical activity may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
1
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(220 citation statements)
references
References 48 publications
5
202
1
12
Order By: Relevance
“…24 In USA the rate of compliance was 38% for dialysis patients. 25 In our study gr-I showed the best compliance followed by gr-III, gr-II and gr-IV. This suggests that an easy and a safe way of exercising has a high rate of compliance among obese cases.…”
Section: Discussionsupporting
confidence: 55%
“…24 In USA the rate of compliance was 38% for dialysis patients. 25 In our study gr-I showed the best compliance followed by gr-III, gr-II and gr-IV. This suggests that an easy and a safe way of exercising has a high rate of compliance among obese cases.…”
Section: Discussionsupporting
confidence: 55%
“…Some earlier studies reported the association of physical activity with survival. Tentori et al reported that mortality risk among HD patients who regularly exercised was 27% lower than that of patients who did not exercise (28). Stack et al also found that HD patients who exercised 2-3 or 4-5 times per week had an approximately 30% lower mortality than those who exercised 0-1 time per week (12).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a list of research recommendations is prepared at the end of all the guideline statements which aims to facilitate future research. RATIONALE: Physical activity levels are strikingly reduced in patients on dialysis (9). There is overwhelming evidence from observational studies that regular exercise improves physical functioning, exercise capacity, and physical performance and has a favourable influence on metabolic profiles (10)(11).…”
Section: No 4 Part I -Management Of Various Cardiovascular Complicmentioning
confidence: 99%